(untitled) (Confluenţe Bibliologice, 2016)
The article is as a family album that covers the life’s chronology and the creative activity of many famous violins and valuable Romanian instrumentalists. It is a memory and remembrance lesson of those who were and are Romanian rhapsodes of music.